Diseño e implementación de un sistema automatizado de agua en todas las instalaciones de la Universidad Técnica de Cotopaxi sede La Maná del cantón La Maná, provincia de Cotopaxi, año 2013 - Pastuña Chicaiza, Luis Gustavo (2015)
We have implemented an automatic dosage of water to the Technical University of Cotopaxi, extension La Mana, which were not available in adequate distribution and chlorination, in order to permanently secure the drinking water. In addition to this, an assessment of the hydraulic system that ensures the design period in terms of its volume and dimensions of pipe is made.